2020
DOI: 10.1136/jclinpath-2020-206800
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and reproducibility among different platforms for tumour BRCA testing in ovarian cancer: a study of the Italian NGS Network

Abstract: IntroductionBRCA tumour testing is a crucial tool for personalised therapy of patients with ovarian cancer. Since different next-generation sequencing (NGS) platforms and BRCA panels are available, the NGS Italian Network proposed to assess the robustness of different technologies.MethodsSix centres, using four different technologies, provided raw data of 284 cases, including 75 cases with pathogenic/likely pathogenic variants, for a revision blindly performed by an external bioinformatic platform.ResultsThe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this context, the robustness of tumor BRCA testing is crucial. In a study within the Italian NGS network, we recently demonstrated that BRCA tumor testing performed with different technologies in different centers may achieve the quality standards for reliability and reproducibility required in the clinical setting [ 30 ]. For 256 cases, the germline BRCA status was available.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the robustness of tumor BRCA testing is crucial. In a study within the Italian NGS network, we recently demonstrated that BRCA tumor testing performed with different technologies in different centers may achieve the quality standards for reliability and reproducibility required in the clinical setting [ 30 ]. For 256 cases, the germline BRCA status was available.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggests the need to integrate BRCA1/2 testing into routine clinical practice ( Figure 1 ). In this setting, NGS, a robust and highly sensitive technology, provides clinicians with the opportunity to comprehensively evaluate BRCA1/2 molecular status in both HGSOC and other types of cancer [ 18 ]. For over a decade now, NGS systems have revolutionized diagnostic practice by improving the success rates of molecular tests even when the diagnostic material is scant.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a plethora of NGS panels are commercially available for BRCA1/2 molecular testing. Despite the high heterogeneity in terms of technical approaches (e.g., chemistry, library preparations, and sequencing analysis) and data analysis (e.g., metrics and bioinformatics pipelines), several studies have long demonstrated a high degree of concordance among the variant cells [ 18 ].…”
Section: Discussionmentioning
confidence: 99%